2015
DOI: 10.12678/1089-313x.19.4.140
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Review of Injury in Pre-Professional Ballet Dancers

Abstract: The objective of this study was to provide an epidemiological review of the literature concerning ballet injuries affecting pre-professional ballet dancers. The literature search was limited to published peer-reviewed reports and involved an extensive examination of Scopus, SPORTDiscus, and CINAHL. The following search terms were used in various combinations: ballet, injury, epidemiology, risk factor, pre-professional, and intervention. Additional citations were located using the ancestry approach. Unlike some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 55 publications
(166 reference statements)
5
54
0
2
Order By: Relevance
“…Identifying the anatomical locations most likely to be injured is of the utmost importance for prevention and one of the most described patterns across the literature. Our findings are in line with previous research where the lower extremity is identified as the most affected body region in preprofessional dancers . Still, in what concerns to specific anatomical locations, some differences exist among studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Identifying the anatomical locations most likely to be injured is of the utmost importance for prevention and one of the most described patterns across the literature. Our findings are in line with previous research where the lower extremity is identified as the most affected body region in preprofessional dancers . Still, in what concerns to specific anatomical locations, some differences exist among studies.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in line with previous research where the lower extremity is identified as the most affected body region in preprofessional dancers. 5,6,8,16,[20][21][22] Still, in what concerns to specific anatomical locations, some differences exist among studies. Within dance training formation, and particularly in classical ballet, the technique and the repertoires have differences between genders, evolving according to SkL.…”
Section: Anatomical Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, only reporting time-loss and/or medical attention injuries underestimates the full extent of injury problems 7. About 90% of overuse injuries will not be registered as an injury when focusing on time loss injuries,8 whereas the majority of injuries by preprofessional ballet dancers (54%–85%) appear to be overused in nature 9. We argue that injury surveillance methods should use inclusive injury definitions 7…”
Section: Introductionmentioning
confidence: 93%
“…In female dancers, overuse injuries to the lower extremities are the most prevalent (Allen, Nevill, Brooks, Koutedakis, & Wyon, 2016). In particular, the extreme positions of pointe work can lead to overuse injuries of the foot and ankle, which is reported to be experienced by 14-57% of female ballet dancers (Smith et al, 2016;Caine, Goodwin, Caine, & Bergeron, 2015;Leanderson et al, 2001). During pointe work, full ankle plantarflexion causes weight bearing forces to be transmitted from the distal phalanges through the metatarsals and stretching soft tissues of the foot.…”
Section: Introductionmentioning
confidence: 99%